(3eSGFd GdGYJbGO heSGFd GdCUhds - (3CHh eMeO Ydj Hf SYjO Hf MRe GdCfOdSjs; (3GHf MRe , CHh eMeOYdj Hf CMeO Hf SYjO Hf MRe GdXGgQj, GHf MRe,J (B456 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO aEfce QZHJe Cf fYed ddeSGFd GdeNJUQI GdJi LeYfGgG ai cJGHfG GdehShe HGdeLdi TQMkG eNJUQkG CjVkG s
(3BNQgG (B:s
(3HYO eG LGA Hg GdbQBf aGdCjI CYe ef Pdc GdNHQ hHGddg JYGdi GdJhajb s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B254 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B17 - (3U (B16s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
Keywords: (3CUhd Gdabgs